Modification of glass structure via CaO addition in granulated copper slag to enhance its pozzolanic activity. (20th April 2020) - Feng, Yan; Chen, Qiusong; Zhou, Yanlong; Yang, Qixing; Zhang, Qinli; Jiang, Liang; Guo, Hongquan
Highlights: The relation between pozzolanic activity and structure properties of GCS was investigated. The existence of ferrous ion behaving as network formers results in a low reactivity of the original GCS. Structural modification with CaO improves the pozzolanic activity of GCS. The incorporation of CaO into GCS favors network depolymerization. Abstract: In present work, the glass structure of granulated copper slag (GCS) is modified by addition of CaO. The pozzolanic activity and structure properties of the modified GCS are evaluated, respectively, by strength test and techniques of FTIR and XPS. Mortars blending the GCS with higher CaO content attain higher strengths at different curing ages. The CaO incorporation interrupts bridging oxygens (BOs) in silicate network as revealed by the FTIR spectra. It also results in an increase in relative concentration of Q 2 structural units, favoring the dissolution of reactive silica. The XPS analysis illustrates one type of BOs being in the linkages of Si–O(BO)–Fe that contribute extensively to the O1s spectrum, which indicates large amounts of ferrous ion (Fe 2+ ) behaving as network formers to co-polymerize with silicate units in tetrahedrally coordinated sites. With CaO of 20 wt% added in the GCS, the NBO (non-bridging oxygen) fraction reaches to the maximum (0.68), corresponding to a low DP (degree of polymerization) for the glassy network, by which the strength of the test mortars reaches to the highest value, confirming strong effects of the structure modification on enhancement of pozzolanic activity.